PENGARUH PENGGANTIAN JAGUNG DENGAN SORGUM Cv. KAWALI DALAM RANSUM PELLET TERHADAP PERFORMANS KELINCI LOKAL - Rumondor, Agung R. P.; Tulung, B.; Rumambi, A.; Rahasia, C.A (Universitas Sam Ratulangi, 2019)
EFFECT OF REPLACEMENT OF CORN WITH SORGUM Cv. KAWALI IN PELLET RANSUM ON LOCAL RABBIT PERFORM. The purpose of this study was to determine the effect of substitution corn with sorghum in rabbit rations on feed consumption, body weight gain, and ration conversion. The duration of the study was 28 days using 20 local rabbits. The statistical design used in this study was a completely randomized design, with 4 (four) treatment rations and 5 (five) replications. The four experimental rations, namely R0: 45% corn + 0% sorghum, R1: 30% corn + 15% sorghum, R2 15% corn + 30% sorghum, R3 0% corn + 45% sorghum. Variables were measured, viz: feed consumption, body weight gain and ration conversion. The results showed that the average of feed consumption, body weight gain, and feed conversion, were: 28.27â€“30.59 g /head /day, 15.76â€“21.55 g / head /day, and 1.42-1.80 g /head /day, respectively. Based on the analysis of variance, the treatments ration had no significant effect (P> 0.05) on consumption, but had a very significant effect (P <0.01) on body weight gain and feed conversion. The LSD test showed that all treatment rations using sorghum (R1, R2, and R3) gave results of body weight gain which were very significantly different (P <0.01) and higher than R0. Whereas, on ration conversion, treatments R1, R2, and R3 give very different results (P <0.01) lower than R0. It is concluded that the substitution of corn with sorghum at the level of 45% in the ration gives the highest results for body weight gain and conversion of rations for rabbits.Â Keywords: corn, sorghum, ration, performance, local rabbit